Histopathological insights into treatment failure with the levonorgestrel releasing intrauterine system in women with heavy menstrual bleeding: a retrospective study - Kumari, Saroj; Mishra, Nigamananda; Kode, Siddhi A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: The levonorgestrel-releasing intrauterine system (LNG-IUS) is an established first-line therapy for heavy menstrual bleeding (HMB), effectively reducing menstrual blood loss and improving quality of life in most women. However, a subset of patients fails to achieve adequate response, warranting evaluation of potential underlying causes. Methods: This retrospective study was conducted at BARC Hospital, Mumbai, from January 2017 to March 2020, and included 88 women with HMB treated with LNG-IUS. Non-responders were identified based on persistent heavy bleeding despite therapy. Endometrial biopsy and, where applicable, hysterectomy specimens were analyzed to determine histopathological findings associated with treatment failure. Results: Of the 88 women treated, 26 (29.5%) were classified as non-responders. Endometrial biopsy revealed proliferative endometrium in 65.4%, disordered proliferative endometrium in 19.2%, and secretory endometrium in 15.4% of cases. Among nine non-responders who underwent hysterectomy, adenomyosis was the most common finding (44.4%), followed by adenomyosis with leiomyoma (33.3%), endometrial polyp (11.1%), and leiomyoma (11.1%). Conclusions: Treatment failure of LNG-IUS in women with HMB was predominantly associated with structural uterine abnormalities, particularly adenomyosis. Comprehensive pre-insertion evaluation, including clinical and imaging assessment, is essential to detect underlying pathology and optimize patient selection. Individualized management based on uterine morphology and symptom profile may improve therapeutic success and reduce delays in achieving symptom control.